Facilitating conditions and social factors as predictors of attitudes and intentions to illegally download - Teah, Min (School of Marketing, Curtin Business School, 2009)
This study investigates the factors influencing downloading behavior of young consumers by examining their attitudes and intentions to download movies and TV series through Peer to Peer (P2P) networks. Regression analysis using data collected from 282 respondents revealed that both facilitating conditions and social factors were significant predictors of attitudes and intentions to download. These results have provided several insightful implications for marketers and policy makers in formulating strategies. New directions for future studies are also discussed.